A comparative study of natural Tunisian clay types in the formulation of compacted earth blocks. (December 2019) - Mkaouar, Safa; Maherzi, Walid; Pizette, Patrick; Zaitan, Hicham; Benzina, Mourad
Abstract: This study investigates the physico-chemical, mineralogical and thermal characteristics of three natural Tunisian clays collected from Gafsa (A1), Zeramdine (A2) and Nabeul (A3). The aim was to promote an appropriate formulation of materials and to obtain optimal compacted earth blocks (CEB). Results of mineralogical analysis of clays revealed the dominance of kaolinite (>13.58%), illite (>25.7%), quartz (>18%) and a minor fraction of smectite phases. Chemical analysis of the clays major elements showed a SiO2 content exceeding 50% and a percentage of Al2 O3 higher than 18%. Particle size distribution showed that clay fractions varied from 10 to 20%. Plasticity index defined a plastic character while the values of specific surface area were around 60 m 2 /g. This discrepancy has an effect on the behavior of these clays in CEB, notably their mechanical properties. From this characterization, it appears that all the sampled clays are suitable as raw material for CEB application. The prepared CEB formulations varied according to compaction energy and binder dosages. In this work, lime served as a binder at different rates (4, 6, 8 and 10%) to ameliorate the quality of CEB. Unconfined Compressive Strength values were determined by Static method test. Then bulk density, shrinkage and porosity values of samples were determined. Compressive strength could reach 7 MPa with lime supplementation in sample A1. The static compaction onto the sand-clay mixture achieved a value of density superior to 2 g cm −3 with lime supplementation in sample A1. Overall, the Gafsa clay was the most suitable for CEB preparation. Also, lime improved the compressive strength of the matrix, in addition to its ecological merits. Highlights: Tunisian clays from Nabeul, Zeramdine and Gafsa were investigated. An ecofriendly and optimal CEB formulation was sought. Mixtures preparation influences physical and mechanical properties of CEB. Lime use as a binder improves mechanical properties of CEB. Correlation could be established between porosity, shrinkage, packing density and strength of the CEB.